BRA Metodik - Balanserad ruttanpassning för mjölkrundetåg i JIT-organiserade monteringsavsnitt - Andersson, Carl; Kype, Björn (My University, 2014)
E2014:043, This thesis aspires to construct a routing optimization method customized for Volvo Powerstrain’s manufacturing plant in Skövde, Sweden. In order to enforce Volvo’s own understanding and control of there own organization, as well as optimize the utilization of the in-house tow trains, the BRO methodology where created. The methodology where created from observations of the currents working environment, analysis of order data as well as a comparison with two similar producing factories. The solution created is limited to be used on in-house tow trains, delivering from a supermarket using milk-runs. It is also adapted, but not limited for use in combination with Kanban and JIT. BRO is a 13-step methodology, divided up into 3 blocks, which utilizes heuristic decision-making and basic resource balancing for laying optimized routes.
Keywords: Övrig industriell teknik och ekonomi; Hållbar utveckling; Transport; Other industrial engineering and economics; Sustainable Development; Transport